The Strong Convex Functions and Related Inequalities. (5th April 2022) - Wang, Xue; Haq, Absar ul; Saleem, Muhammad Shoaib; Zakir, Sami Ullah
Abstract : The study of convex functions is one of the most researched of the classical fields. Analysis of the geometric characteristics of these functions is a core area of research in this field; however, a paradigm shift in this research is the application of convexity in optimization theory. The Jensen-Mercer type inequalities are studied extensively in recent years. In the present paper, we extend Jensen-Mercer type inequalities for strong convex function. Some improved inequalities in Hölder sense are also derived. The previously established results are generalized and strengthened by our results.